Kajian Kapasitas Mayarakat dalam Upaya Pengurangan Risiko Bencana Berbasis Komunitas di Kecamatan Kotagede Kota Yogyakarta Tahun 2016 - Nugraheni, Puspasari Dwi; , Dr. Kuswaji Dwi Priyono, M.Si (2016)
A STUDY OF COMMUNITY CAPACITY IN AN ATTEMPT TO REDUCE THE DISASTER RISKS BASED ON COMMUNITY IN KOTAGEDE DISTRICT, YOGYAKARTA IN 2016 Puspasari Dwi Nugraheni1, Kuswaji Dwi Priyono2 1Student, Faculty of Geography, Universitas Muhammadiyah Surakarta 2Lecturer, Faculty of Geography, Universitas Muhammadiyah Surakarta puspasari.dwinugra@gmail.com E100150008 ABSTRACT Community-Based Disaster Risk Reduction (PRBBK) with involving public society in Disaster Resilient Village (Kampung Tangguh Bencana/ KTB) formed by the Regional Disaster Management Agency (BPBD) is seen as a suitable method to increase the capacity of communities to reduce disaster risks in their area. This study aims to determine the level of hazard, vulnerability level, and community capacity level in risk reduction; and to know the community disaster preparedness in Kotagede District, Yogyakarta in attempt to reduce the disaster risks based on community. The method used in this research is quantitative method by giving scores on secondary data variables and giving questionnaires to determine the level of hazard, vulnerability level, and community capacity level. Qualitative method is used as a backup method by giving interviews to the key figures. The interviews can yield information about people readiness toward disasters. The results indicate that a high level of hazard was found in Rejowinangun Village and Prenggan Village, high level of vulnerability and low level of capacity was found in Prenggan Sub district, thus high level of disaster risk in Prenggan Sub district is a Priority I or the main priority in Kotagede District in disaster risk reduction. Community preparedness in facing disasters is done by establishing three KTB, i.e. KTB Rejowinangun in Rejowinangun Sub district, KTB Darakan in Prenggan Sub district, and KTB Basen in Purbayan Sub district. Keywords: level of hazard, vulnerability level, community capacity level